Diagnosis of chronic thromboembolic pulmonary hypertension. (15th March 2017) - Gopalan, Deepa; Delcroix, Marion; Held, Matthias
Chronic thromboembolic pulmonary hypertension (CTEPH) is the only potentially curable form of pulmonary hypertension. Rapid and accurate diagnosis is pivotal for successful treatment. Clinical signs and symptoms can be nonspecific and risk factors such as history of venous thromboembolism may not always be present. Echocardiography is the recommended first diagnostic step. Cardiopulmonary exercise testing is a complementary tool that can help to identify patients with milder abnormalities and chronic thromboembolic disease, triggering the need for further investigation. Ventilation/perfusion ( V ′/ Q ′) scintigraphy is the imaging methodology of choice to exclude CTEPH. Single photon emission computed tomography V ′/ Q ′ is gaining popularity over planar imaging. Assessment of pulmonary haemodynamics by right heart catheterisation is mandatory, although there is increasing interest in noninvasive haemodynamic evaluation. Despite the status of digital subtraction angiography as the gold standard, techniques such as computed tomography (CT) and magnetic resonance imaging are increasingly used for characterising the pulmonary vasculature and assessment of operability. Promising new tools include dual-energy CT, combination of rotational angiography and cone beam CT, and positron emission tomography. These innovative procedures not only minimise misdiagnosis, but also provide additional vascular information relevant to treatment planning. Further research is needed to determine how these modalities will fit into the diagnostic algorithm for CTEPH. CTEPH is a curable form of pulmonary hypertension which requires multimodality imaging for accurate diagnosis http://ow.ly/oTVT308CcD4